The impact of divorce and the right to the custody of children in non-Muslim family law / Badrah Yussof - Yussof, Badrah (faculty of Law, 1985)
This paper introduoes the nature of marriage and its subsequent duties and liabilities. A failed marriage usually brings about many problems and divorce is a remedy provided by the statute to try and help the aggri eved party. Usually when the spouses separate, the question of custody of children is raised. In this respect laws ensure that children will be protected. The Guardianship of Infants Act 1961 empowers the court to ensure that in deciding matters of custody, the court will regard the welfare of children and shall where the intant has a parent or parents the court will consider the wishes of such parent or both of them as the case mC\)" be. The court will then only consider the wishes of the children when they have attained the age of discernment. Similarly, the relevant provisions under the Law Reform Marriage and Divorce Act 1976. Part VIII, Protection of Children, refer to question of welfare of these children.